2017
DOI: 10.1038/onc.2017.363
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular matrix protein 1 promotes cell metastasis and glucose metabolism by inducing integrin β4/FAK/SOX2/HIF-1α signaling pathway in gastric cancer

Abstract: Extracellular matrix protein 1 (ECM1) is related to strong invasiveness and poor prognosis in major malignancies, but the underlying mechanism remains unknown. Here we aimed to elucidate the function of ECM1 on cell metastasis and glucose metabolism in gastric cancer (GC). The level of ECM1 in sera and tissues of patient with GC were positively correlated with tumor invasion and recurrence. Genetic manipulation of ECM1 expression affected cell metastasis and glucose metabolism in GC cell lines. Enhanced ECM1 e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
96
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(101 citation statements)
references
References 46 publications
0
96
0
1
Order By: Relevance
“…Recent reports pointed at FAK phosphorylation as an important regulator of glucose uptake and consumption . In a previous publication Gan et al ., demonstrated that integrin–FAK signaling pathway resulted into the stabilization of hypoxia‐inducible factor alpha (HIF‐1α) that in turn favored increased glycolysis . In light of our previous results, where TGFBI silencing impaired FAK phosphorylation and downstream AKT, we sought to investigate if this could have an impact on HIF‐1α.…”
Section: Resultsmentioning
confidence: 99%
“…Recent reports pointed at FAK phosphorylation as an important regulator of glucose uptake and consumption . In a previous publication Gan et al ., demonstrated that integrin–FAK signaling pathway resulted into the stabilization of hypoxia‐inducible factor alpha (HIF‐1α) that in turn favored increased glycolysis . In light of our previous results, where TGFBI silencing impaired FAK phosphorylation and downstream AKT, we sought to investigate if this could have an impact on HIF‐1α.…”
Section: Resultsmentioning
confidence: 99%
“…For example, HIF-1α and HIF-2α could promote melanoma metastasis through activating SRC independently [7]. PDGFRA and FAK were also identi ed to be the targets of HIF-1α or HIF-2α and participate in melanomagenesis [27,28]. Besides, HIF1-mediated suppression of melanoma growth could be rescued by MITF overexpression [29].…”
Section: Discussionmentioning
confidence: 99%
“…Manuscript to be reviewed migration, epithelial-mesenchymal transition, invasion, and metastasis in different cancers (Gan et al 2018;Huang et al 2017;Kitajiri et al 2002;Li et al 2017). The aberrant expression of ITGA11, ITGB4, and ITGB8 have been reported in many cancers (Grossman et al 2000;Mertens-Walker et al 2015;Parajuli et al 2017;Tagliabue et al 1998).…”
Section: Discussionmentioning
confidence: 99%